Vantagem competitiva no setor do comércio: criação de valor por meio de métricas contábeis - Mônica Lucindo (2017)
This dissertation is a study of the competitive advantage in the commerce sector. And the main objective of this research is to investigate whether the indicators adopted in this research explain the competitive advantage of firms in the commerce sector, using metrics contained in the structure of the financial statements, verifying the effect of internal and external variables. The motivation of this research is to investigate the capacity that the metrics contained in the structure of the financial statements has to explain the competitive advantage of the company. The research universe consisted of all the companies in the trading sector listed on BM & F Bovespa holding common shares in the period from 2006 to 2016, and the annual data. Of the total of 28 companies 11 were withdrawn due to missing data. It was necessary to standardize the data by means of the following operation: the observed value less than the average divided by the maximum amplitude subtracted from the minimum amplitude due to the difference of scale between the variables. In the study we used the quantitative empirical-analytical scientific method through non-experimental research and the model statistical technique given in short panel, because the analyzed period of 10 years is smaller than the number of companies that compose the sample. The main finding of the research is that the variables that explain the competitive advantage in the commerce sector are: Working capital, Earnings per share, Equity per share and herfindahl index that presented Beta statistically different from zero. The rest of the model variables had betas considered statistically equal to zero. The contribution from the study is to foment debate about the sectors of the Brazilian economy through accounting metrics and external variables around the performance theme.